(untitled) (REMUNOM, 2024)
The increase and demand of the population requires a strengthening in the production of the food necessary for the diet of the same, for this to occur, it is necessary a differentiated care to these sources to generate productivity, without affecting the well-being of these animals. Therefore, the research work aims to bring a diet with higher protein content to the birds, guaranteeing fast weight gain, and the minimum time for slaughter, also emphasizing the importance of protein nutrition in the animal diet, as it represents a significant portion of the costs with nutrients. An exploratory research approach was used, with research surveys of reliable and renowned sites such as Google Academic, Capes Periodicals and Web off Science, compiling information related to the main results on the use of Tenébrio Molitor flour in the feeding of cutting birds. There is a need for alternative sources of protein in animal nutrition due to the increase in the global population and the environmental impact of traditional sources of protein such as soybeans and maize. The inclusion of insect proteins in animal feed can have positive environmental effects, such as reducing greenhouse gas emissions and deforestation. It is concluded that Tenébrio molitor is a promising protein alternative for feeding these animals due to its high nutritional value, low environmental impact and cost-benefit. However, more research and investment is needed to fully develop the production of this protein and its use in animal nutrition.